Performance of nine cassava (Manihot esculanta Crantz) clones across three environments - Boakye-Peprah, B.; Ofori , K.; Asante, I.; Parkes, Elizabeth Y. (Academic Journals, 2013)
The study was carried out to quantify the genotype × environment interaction (G × E) and to estimate the phenotypic stability by genotype genotype × environment (GGE) biplot of nine cassava clones comprising 5 hybrids, 3 parent checks and 1 improved variety. The study was planted across three different environments; Fumesua, Pokuase and Ejura representing forest, coastal savanna and forest transition zones, respectively. Genotype main effect was significant (P < 0.001) for fresh root yield and dry matter content, G × E interaction effect was significant (P < 0.001) for fresh root yield only and environment main effect was significant (P < 0.01) for only fresh root yield. The most stable clone for fresh root yield with above average performance was La02/026 (hybrid). The high genotype and low environment effects, and the relatively low interaction on dry matter content imply that evaluation and selection can be effectively done in fewer environments to select clones with high performance for the trait whiles fresh root yield requires multiple environments to identify clones with broad and specific adaptation.